Everything is possible : antifascism and the left in the age of fascism - Fronczak, Joseph (Yale University Press, 2023)
"In the middle years of the Great Depression, the antifascist movement became a global political force, powerfully uniting people from across divisions of ideology, geography, race, language, and nationality. Joseph Fronczak shows how socialists, liberals, communists, anarchists, and others achieved a semblance of unity in the fight against fascism. Depression-era antifascists were populist, militant, and internationalist. They understood fascism in global terms, and they were determined to fight it on local terms. In the United States, antifascists fought against fascism on the streets of cities such as Chicago and New York, and they connected their own fights to the ones raging in Germany, Italy, and Spain. As he traces the global trajectory of the antifascist movement, Fronczak argues that its most significant legacy is its creation of "the left" as we know it today: an international conglomeration of people committed to a shared politics of solidarity with each other."--Dust jacket.
Keywords: Anti-fascist movements -- History -- 20th century.; Liberalism -- History -- 20th century.; Right and left (Political science) -- History -- 20th century.; Fascism -- History -- 20th century.; Fascism -- Prevention.; Antifascisme -- Histoire -- 20e siècle.; Libéralisme -- Histoire -- 20e siècle.; Fascisme -- Histoire -- 20e siècle.; HISTORY / Modern / 20th Century; Anti-fascist movements; Fascism; Liberalism; Right and left (Political science); 1900-1999; Electronic books.; History